1989
DOI: 10.3109/17453678909149304
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the triangular ligament in Colles' fracture: No effect in a prospective randomized study

Abstract: We present a prospective and randomized study of two different treatments of extraarticular Colles' fracture with a fractured ulnar styloid. The study comprised 41 patients with 2 years' follow-up; 22 patients were treated with closed manipulation and an above-the-elbow plaster cast, whereas in 19 patients the avulsed ulnar styloid was transfixed and/or the triangular ligament was repaired after closed reduction of the fractured radius. In all the operated on patients, a complete rupture of the triangular liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…Reeves (1966) and Burgess and Watson (1988) reported satisfactory results by excision of ulnar styloid fragments for relief of chronic ulnar pain. af Ekenstam et al (1989) found, however, that repair of the ruptured triangular fibrocartilage or avulsed ulnar styloid did not affect the outcome of Colles' fracture. We believe that internal fixation of the avulsed ulnar styloid is not necessary, at least with respect to ulnar wrist pain.…”
Section: Discussionmentioning
confidence: 81%
“…Reeves (1966) and Burgess and Watson (1988) reported satisfactory results by excision of ulnar styloid fragments for relief of chronic ulnar pain. af Ekenstam et al (1989) found, however, that repair of the ruptured triangular fibrocartilage or avulsed ulnar styloid did not affect the outcome of Colles' fracture. We believe that internal fixation of the avulsed ulnar styloid is not necessary, at least with respect to ulnar wrist pain.…”
Section: Discussionmentioning
confidence: 81%
“…[1][2][3][4][5][6][7][8][9] Although nonunion of the ulnar styloid is common after fractures, most nonunions remain asymptomatic despite displacement on radiographs. 8 -13 In symptomatic ulnar styloid nonunions, the origin of the pain may be attributed to abnormal motion from the nonunion site, instability of the distal radioulnar joint (DRUJ), or tear of the triangular fibrocartilage complex (TFCC) with or without DRUJ instability.…”
mentioning
confidence: 98%
“…Of those patients, 44-65% also have an ulnar styloid process (USP) fracture [4][5][6][7]. Displacement of DRFs may result in disruption of the distal radioulnar ligaments, either by direct ligamentous tear or by avulsion of the origin of the ligaments, that is, a fracture at the ulnar fovea or the ulnar styloid [5,6,[8][9][10][11][12][13][14][15][16][17]. Ulnar styloid avulsion may result in distal radioulnar joint (DRUJ) instability due to triangular fibrocartilage complex (TFCC) disruption, the principal stabilizer of the DRUJ [9,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%